Identificación del Riesgo de Incendio Forestal en Líneas de At/Mt de Enel Colombia en la Zona Nororiental de Cundinamarca (2023)
Forest fires are a problem that significantly affects the structure of the soil, which is why early identification of the risk of forest fires in the northeastern area of Cundinamarca, caused by the AT/MT lines belonging to the company ENEL, is important. Colombia.